The Study on How Tax Reform for Acceleration and Inclusion Law (TRAIN) Affects Low-Income Class Families in Manila - Compio, Matthew Cedrick; Cruz, Shawn Gadiel B.; Gaurano, Marion Timothy; Cabauatan, Ronaldo R. (International Journal of Social and Management Studies, 2022)
Abstract This quantitative research is made to investigate the effect of Tax Reform for Acceleration and Inclusion (TRAIN) Law in 100 low income individuals in Tondo, Manila. The examines the effect of the increase and decrease of expenditures on Utilities, Public Transport, Non-Essential Goods and Sugar Beverages in their Disposable income when the TRAIN was implemented. This study finds the effect of Train law using a multiple regression model that the respondents residing in Tondo, Manila were affected positively and negatively by the implementation of TRAIN Law.